Propuesta de un plan estratégico para mejorar el nivel de participación de mercado de la empresa Optimus Life E.I.R.L. - Benites Eustaquio, Elvis Yancarlo (2018)
The main objective of this research work is to draw up a proposal for a Strategic Plan to improve the market share of Optimus Life E.I.R.L.; a gymnasium with more than thirteen years in the fitness industry in the district of Trujillo, which It has has lost his market share due to the increase in competitors. The present work begins with the survey of the company's own information; history, organization chart, services, in addition to its current vision and mission. The company's area of influence was defined through a market study, 1.77% was determined as a percentage of current market share for Optimus Life E.I.R.L. and 2.49% as a market capture expectation for 2021. An analysis was made of both the external and internal environment of the company in order to determine its opportunities, threats, strengths and weaknesses. With the information obtained, analyzed and processed through the study's own matrices, the generic differentiation strategy for the company was determined; the alternative external strategies: market penetration, product development and market development. In addition, fifteen specific strategies were defined (seven retained strategies and eight contingency strategies): Reinforce the use of social networks of social networks, as the main means of information, advertising of services and solution of complaints for associates and potential clients; incorporate competency programs between associates and workers on an annual basis; establish alliances and agreements with institutions and companies linked to sports; carry out external sales activations to attract clients; develop alternative sources of income for the company; design and implement a customer management system, identifying key monitoring indicators; incorporate new group disciplines in unused schedules; carry out internal and external campaigns promoting health and sports; implement a system of prices, discounts and special promotions; expand the database of instructors, with their schedules and work centers; train our salespeople in effective sales techniques; define the year of work according to seasons of client influxes; elaborate a marketing plan, based on digital strategies according to the objectives of the strategic plan; update the company's procedures manual, reviewing and redefining processes; implement a performance evaluation system for workers. Finally, with an investment of S/. 9 460, S/. 8 500 and S/. 8 500 for the years 2019 to 2021; the economic evaluation of the proposed Strategic Plan was developed through the NPV and IRR indicators; S/.30 227.3 and 109% respectively, concluding that its implementation is viable and will improve the company's market share.